Yeast and dough: Failed discussions on the European spirit at the International Institute of Intellectual Cooperation (1933-1936) - de Navascués, Santiago (Historia y Política, 2022)
This article examines the main discussions about the European spirit in the intellectual debates sponsored by the League of Nations. Using as a reference the congresses on intellectual cooperation held in various European capitals between 1933 and 1936, we will analyse the perspectives and limits of the reflections on the Europeanism of the intellectuals in the 1930s. Through the documentation of the International Institute of Intellectual Cooperation, you can reconstruct some of the main lines of this reflection developed within the intellectual elites of the time. The study sheds light on the intellectual contradictions raised by the binomial universality and nationalism, or the paradox of a liberal internationalism which, despite the novelty of its proposals, preserved a Eurocentric notion of the world.
Keywords: Europeanism; nationalism; League of Nations; International Committee on Intellectual Cooperation